Assessing integrated phosphorus management practices on crop performance and soil–plant phosphorus dynamics under pearl millet–chickpea system in alkaline Fluvisol - Dutta, Asik; Hazra, Kali Krishna; Nath, Chaitanya P.; Kumar, Narendra; Singh, Raghavendra; Praharaj, C. S.; Patra, Abhik (Frontiers in Sustainable Food Systems, 2025)
Integrated phosphorus (P) management encompassing both conventional and organic sources is a sustainable option to save synthetic fertilizers without compromising crop productivity. Thus, a three 3-year field (2019–2021) experiment has been conducted to assess the impact of six integrated P-management modules on crop productivity and soil–plant P dynamics under pearl millet–chickpea system in the alkaline Fluvisol of Kanpur. The results showed productivity of both the crops increased over the years irrespective of treatments and highest chickpea equivalent pearl millet yield was recorded in 100% recommended dose of P (3.90 t ha−1). Nitrate reductase (61 and 26% in pearl millet and chickpea, respectively) and total chlorophyll had significant jump in 60% recommended dose of P + farm yard manure (5 t ha−1) over control. Soluble P fraction surged by 45% (pearl millet) and 18% (chickpea) in 60% recommended dose of P +crop residue (50%)+ P solubilising bacteria over control with efficient utilization of non-labile inorganic P fractions in both the crops. Higher physiological and internal P use efficiency in control plot indicates efficient use of above ground P under deficiency in both the crops. Correlation study showed grain yield was not significantly interlinked with soil inorganic P fractions in both the crops. Improved physio-chemical condition of soil along continual nutrient and labile carbon availability lead to significant leap in dehydrogenase (27% in pearl millet and 17% in chickpea) and alkaline phosphatase (27% in pearl millet and 31% in chickpea) in 60% recommended dose of P +crop residue (50%)+ P solubilising bacteria over completely fertilized plots in the end of 3 years. In nutshell, it can be inferred that application of 60% recommended dose of P +crop residue (50%)+ P solubilising bacteria along could be an excellent alternative to conventional practices (100% recommended dose of P) certifying higher P-availability and P-use efficacy.